Komitmen, Self-efficacy dan Motivasi: Pengaruh Umpan balik dan Insentif Pada Karyawan Non Manajemen - ., Apriwandi (Jurnal Ilmu Ekonomi ASET, 2011)
Motivating employees to play an important role in the organizationâs successand part of this study indicate a positive relationship between commitment, self-efficacyand motivation. This study tested whether financial incentives and the type of feedbackhad an influence on commitment and self-efficacy in improving performance throughtask motivation. In this study, the proposed variables were the dimension of commitment(affective, continuance and normative) and self-efficacy. The contribution of experimentalstudies in the behavioral accounting literature by investigating how a specific type ofperformance feedback and performance-based rewards affected three dimensions ofcommitment and self-efficacy. Also, in the context of research is relatively easy to investigatewhether the prediction is valid to use for lower-level employees. This experimentparticipants consisted of 84 bachelor degree students of Faculty of Economics andBusiness, Gadjah Mada University. This experimental study resulted that performancefeedback and rewards have no effect on the dimensions of commitment and self-efficacyat the lower level employees. Performance feedback was negatively related to the threedimensions of commitment and self-efficacy, whereas performance-based rewards waspositively related to one-dimensional normative commitment. In addition, the motivationwas not significantly related to two of the three dimensions of commitment and self-efficacy.Normative commitment was significantly positively related to employee job motivationlevel. The implications of this research illustrates that control mechanisms do not goincreasing the commitment and self-efficacy of employees and increased employeemotivation. And the design of incentives and feedback can improve employee performance.Keywords: commitment. self-efficacy, motivation; feedback and incentives